Management Evaluation of Dangerous and Toxic Waste (Infectious and Covid Waste) at the Nusa Tenggara Barat Hospital - Khasanah, Ismatul; Raharjo, Bambang Budi; Wijayanti, Yuni (Universitas Negeri Semarang, 2021)
Dangerous and toxic waste from the Covid-19 pandemic increased by 30 percent. Dangerous waste management is one of the most serious problems in health facilities because a medical waste, especially infectious waste, is very potential in transmitting infectious diseases either through direct or indirect contact through environmental media. The purpose of this study was to analyze dangerous and toxic waste management based on Permenkes No. 7/2019 and Ministry of Environment and Forestry at the West Nusa Tenggara Hospital during the Covid-19 pandemic in 2020. The research design was descriptive qualitative. The data was taken by using the purposive sampling technique, the informants were selected by snowball sampling. The container stage uses yellow plastic, the transportation of covid and infectious B3 waste uses a yellow trolley and the waste transport officer is a cleaning service. Storage of dangerous and toxic waste and covid waste in temporary shelters every other day, if the weather does not support the transportation process for a maximum of one week, treatment of infectious waste and covid waste is carried out by PT PRIA as a third party. The hospital periodically controls related to the implementation of the container, transportation, and storage so that it is always following the applicable of Standard Operation Procedure.